Pelatihan Self Care Management dalam Meningkatkan Kualitas Hidup pada Pasien Diabetes Melitus - Dina Mariana Larira; Adriani Natalia; Nur Anindhita Kurniawaty Wijaya (Jurnal Pengabdian Masyarakat (ABDIRA), 2026)
Diabetes mellitus (DM) is a chronic disease characterized by elevated blood glucose levels, which occurs due to abnormalities in insulin secretion, insulin action, or both. Complications resulting from DM will be experienced by patients throughout their lives, therefore, to reduce these complications, DM sufferers require self-care management. This Community Service Program (PKM) activity aims to empower the community through training on the concept of DM and ways to improve self-care in DM sufferers. The PKM activity was carried out by providing training on DM and self-care management, followed by training in diabetic foot exercises. The results obtained were an increase in participants' knowledge about DM and self-care management, as evidenced by the results of the pre- and post-test. This proves that the counseling that has been conducted has increased participants' knowledge about DM and self-care management. This PKM activity is expected to contribute to increasing participants' understanding of self-care management, thereby improving patients' quality of life.